Joel's use of scripture and scripture's use of Joel : appropriation and resignification in second temple Judaism and early Christianity - Strazicich, John. (Biblical Interpretation Series, 2007)
The methodological approach employed in this research utilizes the hermeneutics of comparative midrash combined with aspects of Bakhtinian dialogism and intertextuality. The purpose of this enterprise is to discern the function of scripture in Joel and its New Testament Nachleben . The terms 'appropriation' and 'resignification' are descriptive of the process through which an antecedent text is transformed by its displacement, condensation, and recontextualization. These methodologies assist in giving an account of the intertextual dialogism involved in a text's unrecorded hermeneutics. The scope of the work looks at the use of scriptural traditions within the book of Joel during the Second Temple period. There is an introduction to the hermeneutical methods employed, followed by a general introduction to the book of Joel in chapter one. Chapters two and three concern the function of scripture in Joel. Finally, the last chapter deals with Joel's New Testament Nachleben. Each chapter has an introduction and conclusion. This work does not eschew the importance of diachronic issues. The diachronic method pays attention to the context of an antecedent's voice, while the synchronic methodological approach pays attention to the function and purpose in which the receptor text resignifies the appropriated motifs and allusions. The diachronic becomes fused with the synchronic in the process of an allusion's recontextualization. This study, in a heuristic manner, focuses on the way that each allusion is appropriated and resignified for the needs of both Joel's community and those of the later NT, in order to understand the function of canonical hermeneutics.